Fabrication of a hyaluronic acid conjugated metal organic framework for targeted drug delivery and magnetic resonance imaging. Issue 12 (9th February 2018) - Shu, Fangpeng; Lv, Daojun; Song, Xian-Lu; Huang, Bin; Wang, Chong; Yu, Yuzhong; Zhao, Shan-Chao
Abstract : DOX-doped MOF nanoparticles were prepared via a one-pot reaction and successively anchored with Fe 3+ and HA for simultaneous targeted drug delivery and MR imaging. Abstract : Since metal organic frameworks (MOF) have exhibited fascinating potential in biomedical applications, it is worthwhile to construct a MOF-based multifunctional drug delivery system. In the present study, the anticancer drug doxorubicin (DOX) was loaded into zeolitic imidazolate framework-8 (ZIF-8) via a one-pot process. The formed DOX@ZIF-8 was then coated with polydopamine, successively chelated with Fe 3+ and conjugated with hyaluronic acid (HA), finally resulting in a multifunctional ZIF-8 nanocarrier. The characterization results confirmed the successful formation of the hybrid nanocarrier. pH-responsive drug release of DOX was observed due to the innate pH-dependent stability of ZIF-8. Importantly, the flow cytometry and confocal laser scanning microscope results both verified the targeting ability of DOX@ZIF-HA toward prostate cancer PC-3 cells. The improved therapeutic efficacy of DOX@ZIF-HA when compared to the inhibited group was also demonstrated. Furthermore, the chelation of Fe 3+ by PDA makes the prepared DOX@ZIF-HA a good contrast agent for magnetic resonance (MR) imaging. Hence, we hope the constructed ZIF-8 based multifunctional nanocarrier could be a candidate for cancer theranostics.